Short Sleep Duration on the Night Before Surgery Is Associated With Postoperative Cognitive Decline in Elderly Patients: A Prospective Cohort Study - Takamino, Ayasa; Kotoda, Masakazu; Nakadate, Yosuke; Hishiyama, Sohei; Iijima, Tetsuya; Matsukawa, Takashi (Frontiers in Aging Neuroscience, 2022)
As the world is rapidly aging, and the number of elderly patients who undergo surgery is rising, postoperative cognitive decline among those patients has become an increasing healthcare problem. Although understanding the risk factors and mechanisms underlying the pathogenesis of postoperative cognitive decline is critically important from a preventative viewpoint, such knowledge and evidence are lacking. A growing body of evidence suggest an association between cognitive function and sleep duration. The purpose of this study was to investigate the association between postoperative cognitive function and sleep duration on the night before surgery using a wearable sleep tracker. In this 6-month prospective cohort study, we analyzed data from 194 patients aged ≥ 65 years who underwent elective non-cardiac and non-cranial surgery under general anesthesia. According to the sleep duration on the night before surgery, patients were categorized into following four groups: <5, 5–7, 7–9, and >9 h. Perioperative cognitive function and domains were assessed using a neuropsychological test battery, and the incidence and prevalence of cognitive decline over 6 months after surgery were analyzed using the multiple logistic regression analysis. During the 6-month follow-up period, 41 patients (21%) developed cognitive decline. The incidence of cognitive decline was significantly elevated for the patients with sleep duration < 5 h (vs. 7–9 h; surgical duration-adjusted odds ratio, 3.50; 95% confidence interval, 1.20–10.2; P < 0.05). The association between sleep duration and prevalence of cognitive decline was limited to the early postoperative period (at 1 week and 1 month). Among the cognitive domains assessed, attentional function was significantly impaired in patients with a sleep duration < 5 h [vs. 7–9 h at 1 week; 4/37 (10.8%) vs. 0/73 (0%); P < 0.05]. In conclusion, sleep duration < 5 h on the night before surgery was significantly associated with worse attentional function after surgery and higher incidence of cognitive decline. The present results indicate that sleep deprivation on the night before surgery may have a temporary but significantly negative influence on the patient's postoperative cognitive function and is a potential target for preventing cognitive decline.